American and Moroccan undergraduates encounter religious difference: an exploratory study - Henseler, Sarah (Journal of beliefs and values, 2024)
As emerging adult college students ponder their religious/spiritual beliefs and identities, those in religiously diverse countries (e.g. the USA) often encounter beliefs different from their own. These encounters can prompt new perspectives on their own beliefs and elicit responses from rejection to incorporation of the diverging belief, thus shaping students’ beliefs and identities going forwards. But do undergraduates in religiously homogeneous countries like Morocco have similar experiences of encounter and response? Here, 213 American and 78 Moroccan English-language university students wrote descriptions of encounters with, and responses to, others’ dissimilar religious views. Comparisons revealed expected differences (more self-chosen identities among those in the diverse context; older age at the encounter in the homogeneous context) and striking similarities (frequency of encounters with atheism; interpersonal relationships as the most common encounter setting). Across both samples, ‘incorporating others’ belief’ was the rarest response to encountering a difference, and women were more open to learning about divergent beliefs than men were. The roles of local and global contexts in exposure and response to religious diversity are discussed.